A Comparative Study of Child Abuse Risk Assessment in the United States and Korea. Issue 2 (1st June 2016) - Hyun, Jinhee; Adams, Sheila R.
Abstract : The perceptions and judgments of social workers who interview the child and family are especially significant factors in child abuse assessment process. The current study describes and compares child protection workers' assessment processes in Korea and the USA through the use of case vignettes and in‐depth interview. The responses from social workers in these two countries were compared and discussed in the areas of: risk assessment; perception of the main problems; tolerance of corporal punishment; and judgments about appropriateness of interventions. Most revealing was that Korean social workers determined abuse based on their child abuse definition and the US Army FAP social workers determined abuse based on their definition, which was affected by legal standards and cultural differences. Korean social workers are more likely to remove a child from the home, even in mild cases, but US FAP social workers would recommend child removal from the home as a last option. The social workers that participated in this survey play a vital role in the safety of children in child protective services. Both countries can benefit from sharing information to improve the child protection services delivered. Social workers' professional judgment leads to objective and consistent outcomes and are less likely to compromise child safety in the decision making process.